2017
DOI: 10.4103/jisppd.jisppd_115_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic dental injuries among visually impaired children attending special schools of Chhattisgarh

Abstract: As blind children are at the risk of multiple TDI, it is necessary to create awareness, health education, and periodic screening for appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 0 publications
3
26
1
Order By: Relevance
“…Falling and collision were the most reasons for traumatic injuries, this was logic as blind children are more liable to fall and crash against different objects than being involved in violent activities. These results were in agreement with the results of Agrawal et al (22) Munot et al (24) .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Falling and collision were the most reasons for traumatic injuries, this was logic as blind children are more liable to fall and crash against different objects than being involved in violent activities. These results were in agreement with the results of Agrawal et al (22) Munot et al (24) .…”
Section: Discussionsupporting
confidence: 94%
“…Most of TDIs affect the central incisors .There were significant correlations between increased overjet and/or inadequate lip coverage and prevalence of TDIs. This is in agreement of all the studies which correlate the prevalence of TDIs and the degree of overjet and lip coverage (1,14,16,(22)(23)(24)(25) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…39%) were found to be the second most common cause for early tooth loss in patients who were 16-18 years old and 13 to 15 yr old as per the results of the study. Harsha et al's study has shown the similar results that 39% of the children suffered from traumatic dental injuries (Munot et al, 2017). Next reason being congenital missing teeth ,the study done by Masamichi Ide et al(Ide et al, 2011) observed that 11.7% of the children had congenitally missing teeth,similar results were obtained in our study.In our study, among 16 to 18 yr old ,molars (31.50%) accounted for the most commonly lost permanent teeth, Alshamrani et al study too stated that 21.3% had early loss of permanent molars(Alshamrani et al, no date).…”
supporting
confidence: 89%